AI-Powered Robo-Advisors: Opportunities and Challenges in Cloud-Based Financial Services - Sankaralingam, Kuthalingam (International Journal of Computing and Engineering, 2025)
Purpose: The convergence of artificial intelligence (AI) and cloud computing has significantly transformed the financial services sector, particularly within the domain of robo-advisors. Methodology: These platforms employ advanced algorithms to deliver investment guidance with minimal human oversight. By leveraging Amazon Web Services (AWS), financial institutions can greatly enhance their operational scalability, efficiency, and the overall intelligence of their service offerings. Findings: This paper examines the emergence of AI-driven robo-advisors hosted on AWS, exploring the advantages, technical architecture, and the regulatory and ethical challenges they encounter. We provide real-world case studies that illustrate the current strategies being adopted by financial organizations. Additionally, a detailed flowchart offers insight into the system architecture of cloud-based robo-advisors, demonstrating the interaction between data inputs, processing algorithms, and user interfaces. Unique Contribution to Theory, Practice, and Policy: This analysis seeks to inform industry practitioners about the dynamic landscape of digital wealth management and the potential paths for future innovations in this field.